Effects of heat adaptation on physiology, perception, and exercise performance in the heat: an updated meta-analysis - Tyler, C. J.; Reeve, T.; Sieh, N.; Cheung, S. S. (Journal of Science in Sport and Exercise, 2024)
Purpose Heat adaptation (HA) is a popular strategy to combat the negative effects of thermal stress. The HA literature has expanded since a 2016 meta-analysis, and we provide an updated meta-analysis, incorporating 39 additional studies and advanced analysis.